al-Akhtha' al-Syai'ah fi Tarjamah al-Ta'birat al-Ishthilahiyah li Mona Baker fi Riwayah al-Hub tahta al-Mathar li Najib Mahfouz - Alfatha, Shidik; Yasmadi, Yasmadi; Asrina, Asrina (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2024)
This study aims to discuss common errors in translating idioms found in the literary novel al-Hub tahta al-Mathar by Najib Mahfouz, which was translated into Indonesian under the title Rinai Cinta. There are discrepancies in meaning between the source language (Arabic) and the target language (Indonesian), resulting in misinterpretations for non-Arabic readers. This research is significant in preserving the authenticity of the source language and contributes to producing more accurate and high-quality translations. To analyze the types of translation errors, the researcher employed Mona Baker's translation theory from her book In Other Words. This study is a library research project utilizing a qualitative approach with a descriptive-analytical method. The findings reveal 12 types of idiomatic translation errors in the novel. When analyzed using the theoretical framework, the translation does not align with the strategies proposed by Mona Baker, thus classifying these as